Knowledge-Management-Based-Nursing Care Model Improves Patient Adherence to Tuberculosis Treatment - Ninuk Dian Kurniawati; Abu Bakar; Eka MHas; Elida Ulfiana; Laily Hidayati; Hanik Endang; Retnayu Pradanie; Kristiawati Kristiawati; Erna Dwi W (Universitas Airlangga, 2016)
Introduction: Pulmonary tuberculosis remains prominent as one of public health problems in the world. Patients’ non-compliance to treatment is a significant contributor to drug resistance. This study aimed to develop and to test the efficacy of a nursing care model to prevent non-compliance.Methods: This study consisted of two phases: phase one, model development, used a descriptive analytic, and phase two, model testing, employed a quasi-experimental design. Participants, comprised both patients and nurses at two health care centres in Surabaya, were recruited by consecutive sampling. Data were collected by interview, self-administered-questionnaires, check-list and focused group discussion. Data analyses were performed using both partial least squares and Wilcoxon signed rank test.Results: The model was statistically effective to improve nearly all aspects of patients’ compliance to TB treatment (knowledge, discipline in taking medications regularity of controls, and abilities to monitor the results of treatment with p < 0.05), except for abilities to cope with drug adverse effects (p = 1.000). This is possible because seldom do patients aware of the medication side effects, so their experiences were probably limited.Conclusion: This study concludes that the KM nursing care model was proven effective to improve patients’ adherence to treatment. Future study is suggested to evaluate the impact of the KM nursing care model in bigger population.